Examining co-activation through cross-linguistic influence among bilinguals in spoken language processing: evidence from eye movements - Soh, Or-Kan; Hazita Azman,; Ho, Su Mei (Penerbit Universiti Kebangsaan Malaysia, 2020)
The aim of this paper is to examine the cross-linguistic influences of both early and late bilinguals in spoken language processing and the differences between them. There were four undergraduates, comprising of two early and two late bilinguals, participated voluntarily in this research. The Tobii X 300 was used as the equipment to be applied when measuring and recording the eye-movements of students. Four conditions, namely between competition, within competition, simultaneous competition, and no competition, were designed as the stimuli. Findings were coded as containing zero or greater-than-zero fixations of each condition (if it was present) along with their respective filler (control). The presence of competition can be measured by employing time course sensitive response measures which is the time to first fixation. The results of this study have illustrated through the presence of cross-linguistic influence in bilinguals that the two languages in the bilinguals mind exist in a state of co-activation regardless of their age of acquisition, consistent with previous studies conducted. However, the age of acquisition of a bilingual’s second language differentiates the type of cross-linguistic influence that a bilingual is likely to face when processing their second language.